Strategies employed by the head teachers in the implementation of competence-based curriculum in public primary schools in Bagamoyo, Tanzania - Beatrice Mlenge; Asia Mbwebwe Rubeba; Huruma Olofea (Освітній вимір, 2025)
This study examined strategies employed by the head teachers in implementing a competence-based curriculum (CBC) in public primary schools in Bagamoyo District, Tanzania. The study adopted a qualitative research approach, with a case study research design, for the purpose of determining in-depth information regarding the implementation of CBC. The study involved 10 participants, thus head teachers. Interviews, observation and documentary reports were used to collect field data. The data were analysed thematically. The findings reported that the head teachers employed various strategies to support teachers in adapting to CBC in public primary schools, namely improving in-service teacher training, teaching and learning materials, the teaching and learning environment, teaching and learning resources, as well as facilitating the relationship between school and community. However, some challenges were noted to hinder the effective implementation of CBC, including a lack of resources, a large number of students in the classroom, and a lack of competent teachers to implement CBC effectively. The study concludes that it is important for the head teachers to devise numerous strategies that could be used for effectively implementing CBC in primary schools. The study recommends that the government, private sectors, and non-governmental organisations ensure the availability of teaching and learning resources, enough teachers, and a good learning environment, as well as training about implementing CBC for all primary school teachers.